Labial and palatal alveolar bone changes during maxillary incisor retraction at the Universitas Sumatera Utara Dental Hospital - Suci Purnama Sari; Mimi Marina Lubis; Muslim Yusuf (Dental Journal, 2022)
Background: The fundamental concept of tooth movement during orthodontic treatment is the occurrence of bone remodelling accompanied by tooth movement in equal proportions. The thickness of the alveolar bone, which supports incisors, is important in estimating the direction of tooth movement. Purpose: The study aimed to measure labial and palatal alveolar bone thickness changes after maxillary incisor retraction using lateral cephalograms. Methods: Cephalograms of 40 patients (18.58 ± 4.2 years) with skeletal Class I bimaxillary protrusion after maxillary first premolar extraction for insisivus retraction had been taken before (T0) and after (T1) orthodontic treatment. Changes in alveolar bone thickness were measured in linear and angular directions and then analysed with Spearman correlative analysis. Then the samples were separated into two groups based on the type of tooth movement (tipping and torque), and then the data were analysed using Wilcoxon analysis to see differences in the bone thickness (p<0.05). Results: There was a significant difference in the apical palate (p<0.05) and a relationship between retraction and alveolar bone thickness in the midroot area. In the angular direction, there was no significant difference and relationship; however, there was a significant difference in the labial crestal in the tipping group. In the torque group, the difference in bone thickness occurred in the crestal and apical palatal areas. Conclusion: The retraction and the type of tooth movement difference influence the alveolar bone thickness.